Діагностування напруженого стану надземних переходів магістральних нафтопроводів - Білобран, Богдан; Дзюбик, Андрій (КІНПАТРІ ЛТД, 2013)
The influence of the mounting pressures on the strength of the transition overhead pipeline. An accounting-experimental methods of diagnosing stress-strain state transitions.
Diagnosis of stress state transitions aboveground oil pipelines